Parental styles and bullying behaviour, in adolescents and young adults: Moderating effect of personality - Mota, Catarina Pinheiro (2019)
The emotional nature and the relationship between parents and their children, characterized by the parental styles, display an important contribution to the psychosocial development of adolescents. The adolescent personality is shaped by their family environment and the relationship with their peers, which have a big significance to the future behaviour of the adolescents and young adults. The present study aims to analyze predictor role from parenting styles of both mother and father with the adolescent personality in different bullying behaviours, and also, evaluate the moderating role of personality traits on the association between parenting styles and bullying behaviours. The study sample consisted of 1,976 adolescents and young adults aged between 14 and 25 years old (M=17:22, SD=2.50). Data collection was performed using a self-report instrument. The results suggest the extraversion and conscientiousness traits as protective factors to the victimization and aggression behaviours, and neuroticism trait as an enhancer of these behaviours. The results will be discussed in light of Baumrind theory, assuming the importance of parenting styles for the personality and behaviour development in adolescents and young adults.